High proportions of liver fibrosis and cirrhosis in an ageing population of people who use drugs in Amsterdam, The Netherlands. Issue 10 (October 2018) - van Santen, Daniëla K.; Schim van der Loeff, Maarten F.; Cartier van Dissel, Judith; Martens, Jonie P.D.; van der Valk, Marc; Prins, Maria
Abstract : Background: The incidence and prevalence of hepatitis C virus (HCV) infection among people who use drugs (PWUD) peaked in the 1980s in Amsterdam. As liver cirrhosis develops several decades after HCV infection and PWUD have other risk factors for liver fibrosis, we hypothesized that significant liver fibrosis or cirrhosis is now common among PWUD in Amsterdam. Methods: PWUD were recruited from the Amsterdam Cohort Studies, methadone programmes and addiction clinics during 2009–2016. Transient elastography was performed to assess liver stiffness. We estimated METAVIR fibrosis levels on the basis of the following liver stiffness measurements (LSMs) cut-offs: F0–F2 (no/mild) less than 7.65 kPa; F2–F3 (moderate/severe) at least 7.65 to less than 13 kPa; and F4 (cirrhosis) at least 13 kPa. Using linear regression models, we assessed the association between LSM and sociodemographic, clinical and behavioural determinants in (a) all PWUD and (b) chronic hepatitis C virus (cHCV)-infected PWUD. Results: For 140 PWUD, the median LSM was 7.6 kPa (interquartile range=4.9–12.0); 26.4% had moderate/severe fibrosis and 22.9% had cirrhosis. Of 104 chronically infected PWUD, 57.7% had evidence of significant fibrosis (≥F2). In multivariable analysis including all PWUD, increased LSM was associated significantly with cHCV monoinfection and HIV/HCV coinfection. In cHCV-infected PWUD, older age was associated significantly with increased LSM. In all groups, longer duration of heavy alcohol drinking was associated with increased LSM. Conclusion: A high proportion of PWUD had significant fibrosis or cirrhosis that were associated with cHCV infection, HIV/HCV coinfection and duration of heavy alcohol drinking. Increased uptake of HCV treatment and interventions to reduce alcohol use are needed to decrease the liver disease burden in this population.